2021
DOI: 10.1016/j.abd.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leiomyosarcoma: a 20-year retrospective study and review of the literature

Abstract: Background Cutaneous leiomyosarcoma is a rare malignant neoplasm with muscular origin, representing 2%-3% of all cutaneous soft tissue sarcomas. Objectives The aim of this study was to characterize clinicopathological features of patients diagnosed with cutaneous leiomyosarcoma in our center over the last 20-years. Methods A retrospective study of patients with a histopathological diagnosis of leiomyosarcoma between 1999 and 2018 was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
(58 reference statements)
0
19
0
1
Order By: Relevance
“…Radiotherapy can also be used in local palliative control in cases with metastases. 9,10 Regarding prognostic factors, there are few studies in which only the size of the tumor was shown to be an independent prognostic factor in relation to decreased survival. Factors such as a tumor size equal to or greater than 5 cm, deep location with involvement of the fascia, and a high histological grade were correlated with lower survival.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy can also be used in local palliative control in cases with metastases. 9,10 Regarding prognostic factors, there are few studies in which only the size of the tumor was shown to be an independent prognostic factor in relation to decreased survival. Factors such as a tumor size equal to or greater than 5 cm, deep location with involvement of the fascia, and a high histological grade were correlated with lower survival.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma is a rare malignant neoplasm that arises from smooth muscles and accounts for about 3% of all soft-tissue sarcomas. 2 This type of tumor is most prevalent in White men ages 50 to 70 years. 3 The two types of superfi cial leiomyosarcomas are • Cutaneous, which develop from the arrector pili muscle and have an overall good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma is a rare malignant neoplasm that arises from smooth muscles and accounts for about 3% of all soft-tissue sarcomas 2. This type of tumor is most prevalent in White men ages 50 to 70 years 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der „dermatologische Patient“ hat gelegentlich eine Traumaanamnese und ist mittleren Alters, eher unter 50 Jahre. Der LMS-Patient mit tiefem LMS ist älter und taucht eher in der Orthopädie auf mit „Tumor im Muskel“ an den Extremitäten 23 24 25 .…”
Section: Atypisches Fibroxanthom – Low Risk (Afx) Und Pleomorphes Der...unclassified